Susceptibility of Staphylococcus species and subspecies to fleroxacin. - Bannerman, T L (1991)
Twenty-four Staphylococcus species or subspecies were examined for their susceptibilities to the fluoroquinolone fleroxacin (Ro 23-6240) by disk diffusion (5-micrograms disk) and by agar dilution for the determination of MICs. Resistant strains were further tested for their susceptibilities to oxacillin and the fluoroquinolone ciprofloxacin. Reference strains of the novobiocin-resistant species (Staphylococcus saprophyticus, Staphylococcus cohnii, Staphylococcus xylosus, Staphylococcus arlettae, and Staphylococcus gallinarum) had an intrinsic intermediate susceptibility (MIC, 4 micrograms/ml) to fleroxacin. Fleroxacin resistance was not observed in the reference strains of the novobiocin-susceptible species (MIC, 0.5 to 2.0 micrograms/ml). Clinical isolates of coagulase-negative species were generally less susceptible to fleroxacin than were reference strains. Seven percent of the Staphylococcus epidermidis clinical strains were resistant (MIC, greater than or equal to 8 micrograms/ml) to fleroxacin. Of these strains, 77% were resistant to oxacillin and 50% were resistant to ciprofloxacin. Thirty-four percent of the Staphylococcus haemolyticus clinical strains were resistant to fleroxacin, and 9% had intermediate susceptibility. Of the resistant strains, 95% were resistant to oxacillin and 77% were resistant to ciprofloxacin, while 23% had intermediate susceptibility to ciprofloxacin. Fleroxacin is an effective antimicrobial agent against most staphylococci.